THE MANIFESTATION OF THE TEGAL LEARNING CENTER (TLC) COMMUNITY’S ROLE IN PROVIDING ACCESS TO HIGHER EDUCATION - Nurfaizzatu Dzikrillah; Nurul Fatimah (Jurnal Analisa Sosiologi, 2025)
Access to higher education is crucial for students. Examining how the Tegal Learning Center (TLC) community contributes to improving education in Tegal City by offering free higher education is the goal of this study. The concepts of inclusive education and role theory specifically, the manifest and latent functions proposed by Robert K. Merton are used to frame the study. Eight informants three TLC board members, three scholarship recipients who also volunteer for TLC, and two students who take part in TLC activities were used in the qualitative descriptive study design. In order to validate the data, source triangulation was employed in conjunction with observation, interviews, and documentation as data gathering methods. Through data reduction, data display, and conclusion drafting, the data were examined. Findings from this study reveal that the TLC community plays multiple roles, including facilitator, educator, mentor, motivator, and evaluator. Among TLC's obvious functions are enhancing the caliber of human resources, offering scholarships, facilitating regional education and learning, and creating a forum for young people's goals and cooperation. Its latent purposes, meanwhile, include encouraging educational equality, boosting self-esteem, connecting people, and driving social change. These results advance our knowledge of how education, social structure, and social mobility interact, and they also help to build more inclusive, participative, and socially conscious community-based education.